The effect of marketing mix on purchase intention in spa at Bandar Hilir, Melaka / Noorliana Jaslin , Nor Syahira Mohd Khalid and Nurul Nabilah Ab Manan - Jaslin, Noorliana; Mohd Khalid, Nor Syahira; Ab Manan, Nurul Nabilah (Faculty of Hotel and Tourism Management, 2015)
This study investigates the effect of the marketing mix on purchase intention in spa at Bandar Hilir, Melaka. The marketing mix that are used is 4P's that is product, promotion, place and price. Purchase behavior is an important key for consumers during considering and evaluating of certain product. Problem that faces is Malaysian spa industry experiences a shortage of skilled labor, many people are still unclear as to what kind of services that a spa offers, and spa industry in Malaysia lack of the National Signature Treatment. The method of data collection that used is questionnaire. The questionnaire were distribute among the tourist in Bandar Hilir, Melaka. The techniques that are used to interpret the data is by using SPSS, Mean, Standard Deviation and also Pearson Correlation. In objective 1, the result indicated that the attitude of the customer were based on their free will and the word of mouth from their members, family or other that can influenced them. While, objective 2 found that, the most preferred marketing mix tools is the strategic location (place) of the Malaysia Spa Industry that can influence the purchasing behavior of customer. However, objective 3 establish that there is moderate relationship between the how the marketing mix are well plan to the attitude of the consumer in purchased the spa services/product maybe the respondents does not clearly understand the spa services.